Cytoprotection of Baicalein Against Oxidative Stress-induced Cardiomyocytes Injury Through the Nrf2/Keap1 Pathway. Issue 1 (January 2015) - Cui, Guozhen; Chui Wah Luk, Sharon; Li, Ronald Adolphus; Chan, Ken Kwok Keung; Lei, Si Wan; Wang, Liang; Shen, Huifang; Leung, George Pak Heng; Lee, Simon Ming Yuen
Abstract : Abstract: Baicalein is one of the major flavonoids found in the root of Scutellaria baicalensis Georgi. Previous studies suggest that baicalein displays protective effect on experimental cardiac models in vitro and in vivo. However, the mode of action remains unclear. Here, we showed that baicalein conferred cardioprotective effect against oxidative stress-induced cell injury in H9c2 cells and human embryonic stem cells-derived cardiomyocytes. Immunoprecipitation with anti-NF-E2–related factor 2 (Nrf2) antibody in baicalein-treated cells demonstrated that baicalein effectively disrupted the association between Nrf2 and Kelch-like epichlorohydrin-associated protein 1 (Keap1). In addition, the unbounded Nrf2 translocated from cytoplasm to nucleus and increased Nrf2/heme oxygenase-1 (HO-1) content in a time-dependent manner. Moreover, antioxidant response element transcriptional activity was enhanced by baicalein treatment, and the Nrf2 siRNA transfection could block the cytoprotective effect of baicalein. Taken together, these results demonstrate that baicalein protected cardiomyocytes against oxidative stress-induced cell injury through the Nrf2/Keap1 pathway.